PEMBERDAYAAN MASYARAKAT DALAM PENGELOLAAN PERTANIAN BERBASIS LINGKUNGAN DAN KEARIFAN LOKAL DI DESA SINDULANG KABUPATEN SUMEDANG - Sofyan, Agus Nero; Permadi, R. Yudi (Unpad Press, 2026)
This community service project is entitled Community Empowerment in Agricultural Management in Sindulang Village, Sumedang Regency Based on Environmental Sustainability and Local Wisdom Principles. The background of this initiative is grounded in the importance of sustainable agricultural systems that are not solely oriented toward increasing production, but also toward maintaining ecological balance and socio-cultural sustainability.This community service activity employs a descriptive qualitative approach with a case study design. Data collection techniques include in-depth interviews with farmers and community leaders, field observations of agricultural practices, documentation, and focus group discussions (FGDs). Data analysis is conducted thematically, referring to the Miles and Huberman model, which encompasses data reduction, data display, and conclusion drawing.The results of this community service activity indicate that agricultural management in Sindulang Village, Sumedang Regency continues to preserve various forms of local wisdom practices, such as mutual cooperation (gotong royong), natural land management, the use of traditional knowledge in determining planting seasons, and efforts to maintain soil fertility and the sustainability of water resources. These practices have been shown to contribute significantly to environmental sustainability and the socio-economic resilience of the rural community.The findings conclude that the integration of local wisdom into agricultural management constitutes an essential strategy in supporting environmentally based sustainable agriculture.